2004
DOI: 10.1051/0004-6361:20034068
|View full text |Cite
|
Sign up to set email alerts
|

HD 173977: An ellipsoidal δ Scuti star variable

Abstract: Abstract. We present spectroscopic and photometric observations of the star HD 173977. It appears that the star is part of a double line binary system, with a period of 1.801 d, corresponding to twice the period of the photometric variations. Hence the star is an ellipsoidal variable. The system is probably synchronized. The physical parameters of both components were derived through two independant methods, one based on evolutionary tracks, the other being the result of the behaviour of light curves in a clos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 12 publications
(14 reference statements)
0
15
0
Order By: Relevance
“…The one prime candidate so far that could not be confirmed as a Doradus star is HD 173977. found it to be a short-period binary and suggested that it might be an ellipsoidal variable. Before we could publish our photometric results confirming this, Chapellier et al (2004) announced HD 173977 to be a double-lined spectroscopic binary with an orbital period of 1.801 days that also exhibits photometric variations caused by both the ellipticity effect and Scuti pulsations. This makes HD 173977 similar to HD 207651 (Henry et al 2004), which appears on Handler's further candidate list.…”
Section: The Samplementioning
confidence: 82%
“…The one prime candidate so far that could not be confirmed as a Doradus star is HD 173977. found it to be a short-period binary and suggested that it might be an ellipsoidal variable. Before we could publish our photometric results confirming this, Chapellier et al (2004) announced HD 173977 to be a double-lined spectroscopic binary with an orbital period of 1.801 days that also exhibits photometric variations caused by both the ellipticity effect and Scuti pulsations. This makes HD 173977 similar to HD 207651 (Henry et al 2004), which appears on Handler's further candidate list.…”
Section: The Samplementioning
confidence: 82%
“…found HD 173977 to be a short-period binary and suggested it might be an ellipsoidal variable. Before we could publish our photometric results confirming this, Chapellier et al (2004) announced HD 173977 to be a double-lined spectroscopic binary with an orbital period of 1.801 days that also exhibits photometric variations caused by both the ellipticity effect and Scuti pulsations. This makes HD 173977 similar to HD 207651 ), which appears on Handler' Basic data for the 11 new Doradus stars in this study are listed in Table 1, with some of their properties determined below.…”
Section: The Samplementioning
confidence: 82%
“…These studies proposed about 60 bona fide and prime candidates stars. One star in our sample, HD 173977, which was in Handler's list (1999), has been discarded since it is now classified as a δ Scuti variable (Chapellier et al 2004). …”
Section: Introductionmentioning
confidence: 99%